2011
DOI: 10.1007/s11434-011-4548-2
|View full text |Cite
|
Sign up to set email alerts
|

Simulated analysis of summer climate on centennial time scale in eastern China during the last millennium

Abstract: Using Lanczos filtered simulation results from the ECHO-G coupled ocean-atmosphere model, this study analyzes the spatiotemporal structure of temperature and precipitation on centennial time scale to examine how climate change in eastern China responded to external forcing during the last millennium. The conclusions are (1) eastern China experienced a warm-cold-warm climate transition, and the transition from the warm period to the cold period was slower than the cold to warm transition which followed it. Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Sporadic precipitation proxies from several different natural archives in local sites and several short‐term time‐slices also showed inconsistent patterns (Shao et al , ; Chu et al , ). Simulation results from the ECHAM4 ‐ HOPE‐G (ECHO‐G) coupled ocean–atmosphere model indicated that more precipitation occurred in the warm periods and less precipitation in the cold periods; the phases (cold spells and warm peaks) of the variations in precipitation lagged behind those of temperature (Wang et al , ). However, there are still large uncertainties in the main spatial patterns of precipitation associated with decadal–centennial cold/warm periods over China and there is inconsistent knowledge of large‐scale dry and wet spatial patterns for the typical warm and cold periods.…”
Section: Introductionmentioning
confidence: 99%
“…Sporadic precipitation proxies from several different natural archives in local sites and several short‐term time‐slices also showed inconsistent patterns (Shao et al , ; Chu et al , ). Simulation results from the ECHAM4 ‐ HOPE‐G (ECHO‐G) coupled ocean–atmosphere model indicated that more precipitation occurred in the warm periods and less precipitation in the cold periods; the phases (cold spells and warm peaks) of the variations in precipitation lagged behind those of temperature (Wang et al , ). However, there are still large uncertainties in the main spatial patterns of precipitation associated with decadal–centennial cold/warm periods over China and there is inconsistent knowledge of large‐scale dry and wet spatial patterns for the typical warm and cold periods.…”
Section: Introductionmentioning
confidence: 99%